2013
DOI: 10.1177/0748233713502839
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ethyl acetate fraction of Lawsonia inermis fruits extract against carbon tetrachloride-induced oxidative damage in rat liver

Abstract: This study aimed to investigate the antioxidant properties of different fractions obtained from the fruits of Lawsonia inermis, a widely used medicinal plant, against carbon tetrachloride (CCl4)-induced oxidative stress in rat liver. The results show that several fractions obtained from L. inermis fruits possessed important antioxidant activity. Among them, the ethyl acetate (EA) fraction showed the highest antioxidant activity. Then, EA fraction was selected for the purification of potential antioxidant compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Pretreatment of rats with ethyl acetate fraction of fruits of Lawsonia inermis at a dose of 250 mg/kg bw and gallic acid significantly lowered some serum alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and lactate dehydrogenase. Ethyl acetate fraction and gallic acid also caused significant reduction in the hepatic thiobarbituric acid reactive substances and increased antioxidant enzymes (superoxide dismutase, catalase, and glutathione peroxidase) in liver from oxidative stress induced by CCl4 [108].…”
Section: Hepatoprotective Activitymentioning
confidence: 95%
“…Pretreatment of rats with ethyl acetate fraction of fruits of Lawsonia inermis at a dose of 250 mg/kg bw and gallic acid significantly lowered some serum alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and lactate dehydrogenase. Ethyl acetate fraction and gallic acid also caused significant reduction in the hepatic thiobarbituric acid reactive substances and increased antioxidant enzymes (superoxide dismutase, catalase, and glutathione peroxidase) in liver from oxidative stress induced by CCl4 [108].…”
Section: Hepatoprotective Activitymentioning
confidence: 95%
“…Research has shown that Lawsonia inermis fruit extracts can protect the liver from oxidative stress induced by carbon tetrachloride (CCl 4 ). 79 Guha et al explored antioxidant activity of L. inermis extracts for preventing Cr(VI)-induced DNA damage. They found that the extracts showed significant potential in scavenging free radicals (DPPH • and ABTS •+ ) and Fe 3+ and in inhibiting LP.…”
Section: Chromium-carcinogenicity Chemopreventionmentioning
confidence: 99%
“…Gallic acid ( 12 ) and its derivative methyl gallate ( 13 ) are the common plant phenolics that have been isolated from the BHP of Lawsonia inermis and showed significant hepatoprotective effect at an IP (intraperitoneal) dose of 294 μ M/kg gallic acid (GA) in CCl 4 -intoxicated rats ( Figure 9 ) [ 170 ]. The study did not reveal any molecular mechanism of GA but demonstrated that the protective effect was observed by lowered serum biochemical parameters, a significant reduction of hepatic ROS, and an increase in antioxidant enzymes, as well as normalized hepatocellular necrosis, vacuolization, and inflammatory cell infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Gallic acid (12) and its derivative methyl gallate (13) are the common plant phenolics that have been isolated from the BHP of Lawsonia inermis and showed significant hepatoprotective effect at an IP (intraperitoneal) dose of 294 μM/kg gallic acid (GA) in CCl 4 -intoxicated rats (Figure 9) [170].…”
Section: Longamentioning
confidence: 99%